Conjugation of photosensitisers to antimicrobial peptides increases the efficiency of photodynamic therapy in cancer cells12. Issue 7 (27th May 2015) - Moret, Francesca; Gobbo, Marina; Reddi, Elena
Abstract : Antimicrobial peptides (magainin, buforin, and apidaecin) are useful tools for increasing the cellular uptake and photodynamic efficiency of photosensitizers. Abstract : Some antimicrobial peptides (AMPs) have the ability to penetrate and kill not only pathogenic microorganisms but also cancer cells, while they are less active toward normal eukaryotic cells. Here we have investigated the potential of three AMPs, namely apidaecin 1b (Api), magainin 2 (Mag) and buforin II (Buf), as carriers of drugs for cancer cells by using the hydrophobic photosensitiser 5-(4-carboxyphenyl)-10, 15, 20-triphenylporphyrin (cTPP) as the drug model, conjugated to the N-terminus of the peptides. Flow cytometry measurements demonstrated that conjugation of cTPP increased its rate and efficiency of uptake in A549 human lung adenocarcinoma cells in the order Mag > Buf > Api. In vitro photodynamic therapy (PDT) experiments showed that the increased uptake of the conjugated cTPP determined 100% cell killing at concentrations in the nanomolar range while micromolar concentrations were required for the same killing effect with unconjugated cTPP. Serum proteins interacted with cTPP conjugated to Buf and Api and slightly interfered with the cellular uptake of these conjugates but not with that of Mag. The data suggest electrostatic interactions of the conjugates with sialic acid and ganglioside rich domains, as lipid rafts of the plasma membrane, followed by cell internalization via non-caveolar dynamin-dependent endocytosis as indicated by the effects of inhibitors of specific endocytic pathways. Our study demonstrated that the three AMPs investigated, Mag in particular, have the ability to carry a hydrophobic cargo inside cancer cells and may therefore represent useful carriers of anticancer drugs, especially those with a poor capacity to penetrate inside the target cells.